Removal of dyes from aqueous solutions by adsorbent prepared from coffee residues. (November 2019) - López, L; Ramirez, A P; Giraldo, S; Flórez, E; Acelas, N Y
Abstract: This study reports the production of an adsorbent material derived from extracted coffee residues using phosphoric acid and zinc chloride as activating agents. The structural features of the materials were characterized using different analytical techniques. The BET surface areas were found between 3.81 m 2 .g −1 y 176.27 m 2 .g −1, while the FTIR analysis showed the formation of oxygenated functional groups, which are active in the adsorption process. These materials were evaluated as adsorbents for the removal of methylene blue from aqueous solution. Batch adsorption tests were performed at room temperature and the effects of contact time and, initial dye concentration was investigated. The equilibrium adsorption results were complied with Langmuir isotherm model and its maximum monolayer adsorption capacity was 15.92 mg.g −1 . Adsorption kinetics studies indicated that the pseudo second order model yielded the best fit for the kinetic data. This typical dependence of methylene blue uptake on kinetic studies indicated the adsorption process to be both chemisorption and diffusion controlled. The experimental data obtained in the present study indicate that coffee residues are suitable candidates for use as adsorbents in the removal of cationic dyes.